Recent progress in bio-inspired macrostructure array materials with special wettability—from surface engineering to functional applications - Zhongxu Lian; Jianhui Zhou; Wanfei Ren; Faze Chen; Jinkai Xu; Yanling Tian; Huadong Yu (International Journal of Extreme Manufacturing, 2023)
Bio-inspired macrostructure array (MAA, size: submillimeter to millimeter scale) materials with special wettability (MAAMs-SW) have attracted significant research attention due to their outstanding performance in many applications, including oil repellency, liquid/droplet manipulation, anti-icing, heat transfer, water collection, and oil–water separation. In this review, we focus on recent developments in the theory, design, fabrication, and application of bio-inspired MAAMs-SW. We first review the history of the basic theory of special wettability and discuss representative structures and corresponding functions of some biological surfaces, thus setting the stage for the design and fabrication of bio-inspired MAAMs-SW. We then summarize the fabrication methods of special wetting MAAs in terms of three categories: additive manufacturing, subtractive manufacturing, and formative manufacturing, as well as their diverse functional applications, providing insights into the development of these MAAMs-SW. Finally, the challenges and directions of future research on bio-inspired MAAMs-SW are briefly addressed. Worldwide efforts, progress, and breakthroughs from surface engineering to functional applications elaborated herein will promote the practical application of bio-inspired MAAMs-SW.